Coarse mesh evolution strategies in the Galerkin multigrid method with adaptive remeshing for geometrically non-linear problems - Feng, Y. T.; Perić, D. (International journal for numerical methods in engineering, 2000)
This paper addresses the strategies of evolving the coarse mesh configurations in the context of the Galerkin multi‐grid (GMG) method when dealing with problems involving large deformations. A new coarse mesh evolution scheme, which continuously and in a simple manner moves the coarse mesh nodal points along with the deformation of the fine mesh, is proposed and its two implementation versions aiming at further improving the efficiency of the scheme are also developed. In addition, the practical aspects of integrating the GMG with adaptive remeshing techniques are discussed. Finally, several large strain elasto‐plastic problems are presented to verify the performances of the proposed schemes and the behaviour of the combined GMG/mesh adaptivity is also illustrated. Numerical results show that up to 40 per cent reduction in the number of MG iterations has been achieved by the new coarse mesh evolution scheme. Copyright © 2000 John Wiley & Sons, Ltd.